Determinants of adherence to anti-TB treatment and associated factors among adult TB patients in Gondar city administration, Northwest, Ethiopia: based on health belief model perspective - Resom Berhe Gebremariam; Maereg Wolde; Aykerem Beyene (BMC, 2021)
Abstract Background Adherence is crucial in treating Tuberculosis to achieve the required treatment success rate. However, due to the longer treatment duration, adherence to Tuberculosis treatment is the most challenging factor affecting Tuberculosis control. Furthermore, although several studies have reported the determinants of Tuberculosis treatment adherence, few of them have used Health Belief Model (HBM) as the guiding principle to determine the individual perception of health-related decisions as much or more than medical concerns with Tuberculosis treatment adherence. Therefore, this study aims to assess adherence to anti-Tuberculosis treatment and associated factors among adult Tuberculosis patients in Gondar city, Northwest Ethiopia, in 2020. Methods Institution-based cross-sectional study was conducted among Tuberculosis patients following anti-Tuberculosis treatment in Gondar city health facilities from February 20 to March 26, 2020. A total of 265 Tuberculosis patients were selected by systematic random sampling techniques that include patients who were on treatment follow up for ≥ 1 month and whose age is ≥ 18 years. Data were collected by trained data collectors using interviewer administer and structured questionnaires. EPI DATA version 4.2 was used for data entry and SPSS version 24 for analysis. The logistic regression model was used to indicate the association between independent variables with adherence to anti Tuberculosis treatment. Results The overall rate of adherence to anti-Tuberculosis treatment was 90.6% within the last 4 weeks and 96.6% within the last 4 days. Multivariable analysis revealed that having treatment supporter [AOR = 3.51, 95% CI (1.15, 10.75)], difficulties in taking TB drugs regularly [AOR = 0.07, 95% CI (0.01, 0.31)], perceived benefit [AOR = 3.45, 95% CI (1.07, 11.08)] and perceived self-efficacy [AOR = 0.22, 95% CI (0.07, 0.63)] were independently associated with adherence to anti-Tuberculosis treatment. Conclusion The treatment adherence rate of the patients was low in the last month before the data survey. Treatment supporters, difficulties in taking anti Tuberculosis drugs regularly, perceived benefit, and perceived self-efficacy were identified as affecting adherence to anti-TB treatment.